A History of the (Attempted) Institutionalization of Parapsychology: Okkultismus im Gehäuse. Institutionalisierungen der Parapsychologie im 20. Jahrhundert im internationalen Vergleich. [Occultism in the housings. Institutionalizations of parapsychology i - Nahm, Michael (Journal of Scientific Exploration, 2020)
In addition to an introduction, the present book contains 14 chapters. Most of them represent elaborated text versions of contributions that were presented by the authors at a (nearly) eponymous conference held in Freiburg, Germany, on the 17.10.2014. As the book title announces, the chapter authors trace the development of parapsychological research in different countries. Usually they focusing on the more or usually less successful attempts to academicize and institutionalize parapsychology as a legitimate scientific discipline, but sometimes they cover also related aspects. The chapters include historical parapsychological treatises for Germany (Ulrich Linse, Anna Lux, Uwe Schellinger, Martin Schneider, Bernd Wedemeyer-Kolwe) including the GDR (Andreas Anton, Ina Schmied-Knittel, Michael Schetsche), France (Renaud Evrard), Great Britain (Elizabeth Valentine), Hungary (Júlia Gyimesi), the Netherlands (Ingrid Kloosterman), Russia in the Soviet and post-Soviet area (Birgit Menzel), and the USA (Eberhard Bauer, Anna Lux). The four chapters covering France, Great Britain, Hungary, and the Netherlands are written in English, the others in German. In the following, will briefly touch upon topics I found most interesting. Anna Lux from the university in Freiburg, Germany, identified several characteristic aspects of academic parapsychological work in Germany and compared them with those in the USA, which took place at about the same time and were more strongly focused on the experimental paradigm. She shows how different social circumstances and also private predilections of the main actors involved resulted in different developments. This also applies to the fate of parapsychology in the other countries mentioned, which is surprisingly multifaceted: While in the Netherlands the situation with official professorships at the University of Utrecht can be compared most closely to that of Germany where Hans Bender (1907-1991) held a professorship at the university of Freiburg, the academization of parapsychology in Hungary was hindered by an influential spiritualist and religious social current. In France, however, comparable efforts were mainly impeded by continued opposition of established scientists. After all, the private research institute “Institute Métapsychique International” (IMI) was founded in France in 1919, which has survived to this day despite adverse circumstances. Great Britain has always played a special role in Western parapsychology, mainly due to the foundation of the “Society for Psychical Research” as early as 1882, which is still considered an international figurehead for a constructive and critical examination of parapsychological topics. However, in Great Britain existed several other societies and “institutes”, which were often small and short-lived. It was not until 1985 that parapsychological research was able to gain a foothold at a British university for the first time through an endowed professorship in Edinburgh, held by Robert Morris (1942–2004) until 2004. From here, numerous graduates were able to carry the work on parapsychological research questions further to other universities.